Myelomeningocele with Unilateral Right Renal Agenesis: A Case Report - Hajime Maeda; Hayato Go; Jun Sakuma; Takashi Imamura; Maki Sato; Nobuo Momoi; Mitsuaki Hosoya (Thieme Medical Publishers, Inc., 2018)
Congenital anomalies of the spine may occur with malformations of the central nervous, cardiovascular, gastrointestinal, respiratory, and genitourinary systems. This is a case of myelomeningocele with unilateral right renal agenesis in a newborn. The patient suffered complications of cerebrospinal fluid leak and meningitis, but was successfully treated and discharged on day 86. In this case, unilateral right renal agenesis represented a significant surgical risk because failure of the remaining kidney could result in renal failure. Because congenital anomalies of the spine may be associated with malformations of the genitourinary system, and additional surgeries were necessary in our case following birth, it is very important that the presence of genitourinary malformations be evaluated.